Problematika Teks dan Makna Matius 19:9 - Adi Putra (Institut Injil Indonesia, 2020)
Abstract: The problematic text and meaning of Matthew 19: 9 is the focus of this study. Because this verse not only causes polemic in its meaning, it is also needed in the text. Because based on the notes to Nestle Aland 28 (NA28), there are so many variations on this verse. By using qualitative, specifically using analysis and exegesis tools with accuracy in analyzing, it is concluded that the text provided by NA28 is much better (stated or) and suitable to be used as translated text in exegesis studies. In addition, in this study, it was found as a phrase